Synchronverter Control for Parallel Operation of Cascaded H-Bridge Inverter - Amar Hamza; Sara Altahir; Xiangwu Yan (Institute of Advanced Engineering and Science, 2016)
A 21-levels cascaded H-bridge multilevel inverter topology based on three-phase voltage source inverter has been proposed as a superior replacement for conventional two-level in high voltage applications. In this work we have presented the usage of the new technique called virtual synchronous generator based synchronverter model to operate the multilevel inverter as synchronous generator, and to share active and reactive power automatically in case of parallel operated inverters of the same type. Carrier-based PWM is used to control each phase leg of the cascaded H-bridge multilevel inverter. This carrier-based PWM scheme is derived from the carrier phase disposition pulse width modulation strategy. By aid of MATLAB/Simulink package a simulation experiment is established to verify the performance of the proposed technique.